THE INFLUENCE OF FERMENTATION AND LONG STORAGE ON THE SILAGE OF CORN TEBON - La Agus (Chalaza Journal of Animal Husbandry, 2016)
The study aims to determine the effect of fermentation time complete feed and silage of Tebon corn to changes in pH and nutrient content. This research was conducted in January to March 2015, in the Laboratory airy College of Agricultural Sciences (STIPER) Kendari and analysis of feed materials to be carried out at the Laboratory of Animal Nutrition and Feed Faculty of Animal Husbandry Haluoleo university. Materials used in this study were aged 60-70 days corn Tebon, pollard 20%; copra 20%; premix 30%; corn Empok 25%; salt 2.5%; minerals 2.5%, Aquadest, a buffer solution pH 7. The catalyst, concentrated H2SO4, distilled water, 0,1N H2SO4, NaOH 40%, indicatormix, 0,1N NaOH. Equipment used in this study include: chopper, plastic, rope scales, vacuum, freezer, Erlenmeyer, pH meter, analytical balance, pumpkin Kjeldhal, Erlenmeyer, glass beaker, destructor, distillation, titration tools, ovens and furnaces. The method used in this study is completely randomized design experiment Nested with 2 treatments, three long storage and 3 replicates (2x3x3) on each treatment. The treatment tested was: Concentrate + Tebon corn with different fermentation time, concentrate + corn silage Tebon with different fermentation time, then do Silage-making, mixing Silage, Silage Testing. The parameters in this study the degree of acidity (pH), nutrient content includes dry matter (DM), organic matter (OM) and crude protein (CP) before and after fermentation. Based on the results of complete feed nutrient content analysis showed that each - each fermentation time treatment effect (P0,01) to change the content of DM, OM and CP when compared to the control with the average low enough pH ranged from 4.18 to 4, 38. Based on this research can be concluded that the fermentation time very real impact on the quality of corn silage Tebon. Fermentation feed concentrate and corn Tebon (KT) decreased nutrient content higher than the complete feed made from concentrates and corn Tebon silage (KS)